Efektivitas Model Pembelajaran Inkuiri Terbimbing Untuk Meningkatkan Hasil Belajar Siswa Yang Dikontrol Dengan Kemampuan Berpikir Kritis - Masruroh, Elok Zakia Ainun; Andrie Wijaya, Shendy; Gerhani, Febrina (UIR Press, 2025)
This study aims to analyze the effectiveness of guided inquiry model compared to conventional model in improving learning outcomes of students who have high and low critical thinking ability and analyze the interaction between guided inquiry model and students' critical thinking ability. This research design uses quasai experiment with factorial design 2 x 2. The population of this research is all students of class XI MAN 2 Jember. The sample of this study was 4 classes taken randomly, namely 2 classes as experimental classes and 2 classes as control classes. The results showed that guided inquiry learning is more effective than conventional learning. Based on the above findings, students can develop their intellectual abilities freely in terms of solving problems. Then the teacher needs to approach, recognize, explore and develop students' learning potentials through cognition of knowledge and experience so far.